ANALISIS POTENSI SUMBER BELAJAR DALAM BUKU ISLAM JALAN TENGAH KARYA YUSUF QARDHAWI - Abdul Fikri; Mukhsin Achmad (Universitas Islam Lamongan, 2023)
The struggles with various phenomena of intolerance and discrimination that occur in the midst of society, especially young people today, make Islamic religious education must increasingly expand learning resources that are not only at the level of normativism alone but more to the effort of comprehensive actualization of Islamic teachings. This study aims to analyze the book Islam the Middle Way by Yusuf Qardhawi as an additional learning resource for Islamic religious education materials. This type of research is included in the qualitative type of library research with the book Islam Jalan Tengah by Yusuf Qardhawi as the primary reference. Data collection used documentation study techniques. Data analysis techniques were carried out descriptively, through the stages of data reduction, data presentation and conclusion drawing. This study concludes that the values of religious moderation from Yusuf Qardhawi's perspective are relevant to the narrative of religious moderation through education by the Ministry of Religion, further to make the book Islam Jalan Tengah by Yusuf Qardhawi as a learning resource can be done through stages: 1) Finding the relationship of the book Islam Jalan Tengah with KI, KD, and PAI learning objectives; 2) Determining the characteristics of PAI material delivery by adjusting input from Yusuf Qardhawi.